1995
DOI: 10.1007/bf00221387
|View full text |Cite
|
Sign up to set email alerts
|

The epidermolytic (exfoliative) toxins of Staphylococcus aureus

Abstract: Two epidermolytic toxins, produced by different strains of Staphylococcus aureus, split human skin at a site in the upper epidermis. Clinical effects are most common in infants, but adults are susceptible. Epidermolysis may also be observed in the mouse, in vivo and in vitro, and in a few other mammals. Recent in vitro experiments have demonstrated an inhibition by chelators and point to metal-ion, possibly Ca2+, involvement. The epidermolysis effect is insensitive to a wide range of other metabolic inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Members of the serine protease family, including V8 protease and the ETs, contain a well-conserved active site, known as a catalytic triad (4,10,11). This motif is characterized by the presence of a highly reactive serine residue within hydrogen-bonding distance of an imidazole ring nitrogen of histidine and a transition state-stabilizing aspartate residue (6,14).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the serine protease family, including V8 protease and the ETs, contain a well-conserved active site, known as a catalytic triad (4,10,11). This motif is characterized by the presence of a highly reactive serine residue within hydrogen-bonding distance of an imidazole ring nitrogen of histidine and a transition state-stabilizing aspartate residue (6,14).…”
Section: Discussionmentioning
confidence: 99%
“…This discussion will focus on the exfoliative toxins of S. aureus and the mechanism by which they cause disease in humans. but not in rats, rabbits, dogs, hedgehogs, voles, guinea pigs, chickens or frogs (Bailey et al, 1995;Elias et al, 1975;Ladhani et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…116 Additionally, other mutations have been identified in patients who have monilethrix hairs as a part of their phenotypic presentation -monilethrix-like congenital hypotrichosis. 110,118 infectious diseases targeting the desmosome Recent research has shown that the desmosome can be targeted during infection. Specifically, the discovery that staphylococcal exfoliative toxins (ETs) can cleave a desmosomal cadherin has shed light on the pathophysiology of a number of blistering diseases with common infective etiology.…”
Section: Desmogleinmentioning
confidence: 99%